(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
Color plays a key role in the field of art, influencing our emotional reactions, enhancing visual aesthetics, and imparting meaning. This scientific article examines the importance of color in art classes, its psychological and aesthetic effects on the creation and appreciation of works of art. By exploring color theory, psychological associations, and practical applications, this article highlights the important role of color in art education. It highlights the benefits of including color studies exercises in visual arts classes to understand color principles, teach color theory, and develop creativity, expression, and visual literacy.